Coumarin-chalcone derivatives as dual NLRP1 and NLRP3 inflammasome inhibitors targeting oxidative stress and inflammation in neurotoxin-induced HMC3 and BE(2)-M17 cell models of Parkinson's disease - Lin, Te-Hsien; Chiu, Ya-Jen; Lin, Chih-Hsin; Chen, Yi-Ru; Lin, Wenwei; Wu, Yih-Ru; Chang, Kuo-Hsuan; Chen, Chiung-Mei; Lee-Chen, Guey-Jen (Frontiers in Aging Neuroscience, 2024)
In Parkinson's disease (PD) brains, microglia are activated to release inflammatory factors to induce the production of reactive oxygen species (ROS) in neuron, and vice versa. Moreover, neuroinflammation and its synergistic interaction with oxidative stress contribute to the pathogenesis of PD. In this study, we investigated whether in-house synthetic coumarin-chalcone derivatives protect human microglia HMC3 and neuroblastoma BE(2)-M17 cells against 1-methyl-4-phenyl pyridinium (MPP + )-induced neuroinflammation and associated neuronal damage. Treatment with MPP + decreased cell viability as well as increased the release of inflammatory mediators including cytokines and nitric oxide in culture medium, and enhanced expression of microglial activation markers CD68 and MHCII in HMC3 cells. The protein levels of NLRP3, CASP1, iNOS, IL-1β, IL-6, and TNF-α were also increased in MPP + -stimulated HMC3 cells. Among the four tested compounds, LM-016, LM-021, and LM-036 at 10 µM counteracted the inflammatory action of MPP + in HMC3 cells. In addition, LM-021 and LM-036 increased cell viability, reduced lactate dehydrogenase release, ameliorated cellular ROS production, decreased caspase-1, caspase-3 and caspase-6 activities, and promoted neurite outgrowth in MPP + -treated BE(2)-M17 cells. These protective effects were mediated by down-regulating inflammatory NLRP1, IL-1β, IL-6, and TNF-α, as well as up-regulating antioxidative NRF2, NQO1, GCLC, and PGC-1α, and neuroprotective CREB, BDNF, and BCL2. The study results strengthen the involvement of neuroinflammation and oxidative stress in PD pathogenic mechanisms, and indicate the potential use of LM-021 and LM-036 as dual inflammasome inhibitors in treating both NLRP1-and NLRP3-associated PD.